On the non-innocence of the imidazolium cation in a rapid microwave synthesis of oleylamine-capped gold nanoparticles in an ionic liquid. Issue 54 (21st June 2018) - Bhawawet, Nakara; Essner, Jeremy B.; Atwood, Jerry L.; Baker, Gary A.
Abstract : We report a very fast (10–30 s) microwave method to prepare oleylamine-capped, monodisperse ca. 8–11 nm gold nanoparticles in an ionic liquid Abstract : We report a very fast (10–30 s) microwave method to prepare oleylamine-capped, monodisperse ca. 8–11 nm gold nanoparticles in an ionic liquid. A pyrrolidinium-based ionic liquid proved an excellent medium for the task whereas, despite their popularity in nanosynthesis, imidazolium ionic liquids gave no colloidally-stable gold nanoparticles in an otherwise identical reaction.